Effect of implementation of a smoke-free policy on physical violence in a psychiatric inpatient setting: an interrupted time series analysis - Robson, Debbie; Spaducci, Gilda; McNeill, Ann; Stewart, Duncan; Craig, Tom; Yates, Mary; Szatkowski, Lisa (Lancet, 2017)
BACKGROUND: Smoke-free policies are important to protect health and reduce health inequalities. A major barrier to policy implementation in psychiatric hospitals is staff concern that physical violence will increase. We aimed to assess the effect of implementing a comprehensive smoke-free policy on rates of physical assaults in a large UK mental health organisation.